A four-decade of abrasive waterjet processing technology (1980-2023): a scientometric analysis - Lusi, Nuraini; Catrawedarma, I Gusti Ngurah Bagus; Gebremariam, Mebrahitom; Saptaji, Kushendarsyah; Azmir, Azhari (EDP Sciences, 2025)
The field of abrasive waterjet (AWJ) machining has seen growing interest over the past decade, reflected in the increasing number of related research publications. Despite significant progress, uncertainties remain regarding the future direction and performance of AWJ technology. This paper aims to deliver a structured, in-depth, dynamic, quantitative, and objective analysis of research in the abrasive waterjet field. By examining the existing body of knowledge and identifying emerging trends, this review seeks to enhance and refine research within the domain of manufacturing. This study employs bibliometric and text mining analyses using R-tool Biblioshiny and VOSviewer to quantitatively assess and visualize key concepts, themes, and research dynamics in AWJ. The dataset, sourced from the Scopus database (1980–2023) following PRISMA guidelines, includes 1,666 articles from 504 sources, involving 3,062 authors across 80 countries and 2,776 affiliations. Findings reveal a significant growth rate of 228.57% in AWJ-related publications in 1993, marking a pivotal increase in scientific output. India and China emerged as the most productive countries in AWJ research. The results provide valuable insights for academics and policymakers, offering a benchmark for evaluating research efforts and guiding future developments in AWJ technology.